(untitled) (Indian Journal of Animal Production and Management, 2024)
Dairy production in India plays an important role in improving the livelihoods of farmers with equity. The milk production in the country has increased by about 10 times since independence (176.35 million metric tons in 2017-18), and at present accounts for about 67% of total value of output from livestock. The dairy production systems are complex and generally based on traditional and socio-economic considerations mainly guided by available feed resources. The traditional feeding system mostly consists of crop by products, natural grasses supplemented with a little or no concentrates. The seasonal fluctuation in availability of fodder from natural pasture and scarcity of feed and fodder resources (both quantity and quality) primarily affect the nutrition in animals, which results in low production and reproductive performance, slow growth rate, loss of body condition and increased susceptibility to diseases and parasites. Low production potential of animals, non-availability of critical inputs/services in time, access to capital and markets also hamper the dairy production. The effective utilization of the available feed and fodder resources and appropriate supplementation of poor quality crop residue and natural pasture appears to be the necessary steps to alleviate the nutritional stress of dairy animals. An array of technologies- feed and feeding interventions have been developed and demonstrated their potential in improving the productivity of dairy animals at field level with varying success. However, enormous efforts are required to upscale and outscale their adoption through different extension agencies by educating farmers on efficient management of limited resources to ensure the long term sustainability and profitability of animal production system. This can be achieved by the favourable policy and actions in terms of access to micro-credit, assured market and veterinary services.